Early puberty associated with the COVID-19 pandemic: systematic review - Martins, Flávia; Sosa, Cecilia Lilian (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: In 2020, the COVID-19 pandemic swiftly escalated into a significant global health emergency. To curb the virus spread, many countries implemented emergency measures such as strict school closures. The pandemic has dramatically impacted the daily lives of children and adolescents, leading to sedentary lifestyles, increased use of electronic devices, and heightened stress-related symptoms. These substantial changes interfere with normal child development. Since the onset of the pandemic, numerous studies have reported an increased incidence of early puberty compared to prepandemic years, with puberty itself progressing at a faster pace. In this review, the aim was to estimate the incidence of new cases of precocious puberty and early puberty during the Covid-19 pandemic. Objectives: The objective of this study is to assess the incidence of early puberty and the progression of puberty during and after the pandemic to compare the results with data from the same period over the last five years and consider potential links between births and data trends. Materials and Methods: This review utilized various databases for article compilation using MESH terminology and identified 09 potential outcomes related to precocious puberty associated with COVID-19